Concentration of Pb (II) by adsorption and its atomic absorption spectrometric determination - Echevarría, Marlene Seijo; Déniz, Rubén del Toro; Sáez, Silvio Martinéz; Juan, Francisco Rosell (Eclética Química, 1997)
A sorption concentration method using impregnated silica has been developed to determine small concentration of lead in water by Atomic Absorption Spectrometry.